The conception of a virtual music course under the eyes of an instructional designer (Research, Society and Development, 2020)
The objective of this work is presenting the project of the course titled "Use of pentatonic scales in the electric guitar" from the perspective of the instructional designer. It is a course inserted in the field of musical education, aimed at teaching a specific instrument, that is, the electric guitar. It has approximately 1 month of duration and counts on theoretical and practical activities, using different media and formats. The virtual environment selected is Moodle, since it is free and has several tools that tend to contribute to the quality of the proposal in line with the different learning styles of the students. Regarding the methodology, in order to present the data and information related to the design of the course, Activity Map were used. In addition, for the theoretical appreciation focused on the interference of the internal and external environments, SWOT analysis was chosen. Through this work, it is identified that the course is financially viable and the quality of the content to be offered make the difference, as well as the pedagogical accompaniment. Thus, it is considered that, independently of the internal and external interferences, the project has potential for the market.